EWSR1 prevents the induction of aneuploidy through direct regulation of Aurora B - Kim, Haeyoung; Park, Hyewon; Schulz, Evan T.; Azuma, Yoshiaki; Azuma, Mizuki (Frontiers in Cell and Developmental Biology, 2023)
EWSR1 (Ewing sarcoma breakpoint region 1) was originally identified as a part of an aberrant EWSR1/FLI1 fusion gene in Ewing sarcoma, the second most common pediatric bone cancer. Due to formation of the EWSR1/FLI1 fusion gene in the tumor genome, the cell loses one wild type EWSR1 allele. Our previous study demonstrated that the loss of ewsr1a (homologue of human EWSR1) in zebrafish leads to the high incidence of mitotic dysfunction, of aneuploidy, and of tumorigenesis in the tp53 mutant background. To dissect the molecular function of EWSR1, we successfully established a stable DLD-1 cell line that enables a conditional knockdown of EWSR1 using Auxin Inducible Degron (AID) system. When both EWSR1 genes of DLD-1 cell were tagged with mini-AID at its 5’-end using CRISPR/Cas9 system, treatment of the (AID-EWSR1/AID-EWSR1) DLD-1 cells with a plant-based Auxin (AUX) led to the significant levels of degradation of AID-EWSR1 proteins. During anaphase, the EWSR1 knockdown (AUX+) cells displayed higher incidence of lagging chromosomes compared to the control (AUX-) cells. This defect was proceeded by a lower incidence of the localization of Aurora B at inner centromeres, and by a higher incidence of the protein at kinetochores compared to the control cells during pro/metaphase. Despite these defects, the EWSR1 knockdown cells did not undergo mitotic arrest, suggesting that the cell lacks the error correction mechanism. Significantly, the EWSR1 knockdown (AUX+) cells induced higher incidence of aneuploidy compared to the control (AUX-) cells. Since our previous study demonstrated that EWSR1 interacts with the key mitotic kinase, Aurora B, we generated replacement lines of EWSR1-mCherry and EWSR1:R565A-mCherry (a mutant that has low affinity for Aurora B) in the (AID-EWSR1/AID-EWSR1) DLD-1 cells. The EWSR1-mCherry rescued the high incidence of aneuploidy of EWSR1 knockdown cells, whereas EWSR1-mCherry:R565A failed to rescue the phenotype. Together, we demonstrate that EWSR1 is essential to prevent aneuploidy through interaction with Aurora B, most likely by regulating the localization of Aurora B at centromere.